Pecking Order and Trade-off Theory in Capital Structure Analysis of Family Firms in Indonesia - Mia Oktavina; Sahala Manalu; Sari Yuniarti (University of Merdeka Malang, 2018)
The purpose of this study has analyzed the determinants of policy decisions of the capital structure of family firms listed on the Indonesia Stock Exchange (IDX) in 2012-2016. The company's capital structure was measured by using debt to equity ratio (DER). Determinants of capital structure used include profitability (ROA), asset structure, growth (growth), firm size (size) and business risk (risk). This research was a quantitative research with a kind of causal research. Using a sample of 38 family companies in Indonesia listed on the Indonesia Stock Exchange (IDX). Hypotheses testing method of multiple linear regression. The result showed that ROA had a negative effect not significant to DER. The asset structure had a significant positive effect on DER, growth had no significant negative effect on DER, size had no significant positive effect on DER, and risk had a significant negative effect on DER. The findings research that the average family firm in Indonesia still uses the Pecking Order Theory in the application of capital structure.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i1.1793